PROBLEMS OF TRANSLATION OF CUSTOMS TERMS IN ENGLISH AND UZBEK LANGUAGES - Mehrinoz Mamurova; Munira Matsapayeva (International Scientific and Current Research Conferences, 2021)
This article discusses the problems of translating customs terms into English and Uzbek. Given the urgency of some of the minor problems of linguistics today, the existing scientific potential is not focused on solving important problems, and the main tasks that determine the future of the industry are still off the agenda.